Two Rare Diseases, One Patient: A Case Report of Mucormycosis and Granulomatous Polyangiitis - Syeda Aasia Batool; Usha Kumari; Salim Surani (Case Reports in Infectious Diseases)
Mucormycosis is a rare but fatal disease caused by a filamentous fungus involving the nose, paranasal sinuses, and brain. These organisms usually cause severe infections in immunocompromised individuals. Granulomatous polyangiitis (GPA), also known as Wegner’s granulomatosis, is a rare, aseptic necrotizing granulomatous vasculitis involving small and medium-sized vessels commonly affecting the nose, ears, lungs, and kidneys. The simultaneous occurrence of mucormycosis and GPA, two rare diseases, in the same patient is exceedingly rare. In this case study, we describe a 40-year-old woman who presented with manifestations of both GPA and mucormycosis. She was started with steroids and antifungal agents and achieved significant improvement.